2019
DOI: 10.2207/qjjws.37.4wl
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Electrode Lifetime and Additive Consumption During TIG Welding

Abstract: The temporal evaluation in the distribution of additives inside the electrode was clarified by the cross-section observation of the electrode after the arc discharge and the numerical simulation. The effect of the adsorption energy of additives on the electrode lifetime was also investigated by the numerical simulation. During the arc discharge, additives whose work function is lower than tungsten are gradually consumed from the electrode tip due to evaporation of additives on the electrode surface and diffusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Time-dependent computations using the model clarified that the additive concentrations gradually decreased from the electrode tip as time passed. These computational results showed the same tendency as the experimentally obtained results [4]. They also indicated that the coverage ratio of the additives on the electrode surface decreased dramatically and that the electrode temperature increased at a certain time.…”
Section: Introductionsupporting
confidence: 84%
“…Time-dependent computations using the model clarified that the additive concentrations gradually decreased from the electrode tip as time passed. These computational results showed the same tendency as the experimentally obtained results [4]. They also indicated that the coverage ratio of the additives on the electrode surface decreased dramatically and that the electrode temperature increased at a certain time.…”
Section: Introductionsupporting
confidence: 84%
“…123,124) Especially in a GTA welding, the transport of emitter additives in a tungsten electrode is also important because it affects the stability of arc discharge and the lifetime of the electrode. The investigations were carried out experimentally 125,126) and computationally. 127) Additionally, the thermal energy transferred from an arc plasma to a base metal was measured for a GTA welding condition.…”
Section: Mpbulkmentioning
confidence: 99%
“…Haidar et al [38] measured the electrode temperature distribution of a free-burning arc with a current of 200 A, electrode diameter of 3.2 mm and tip angle of 60 deg, and found the maximum electrode temperature was about 3600 K that was higher than the melting point of the ThO 2 emitter material. Tanaka et al found that during the high current TIG welding, the tungsten electrode was also melted [39]. As shown in figure 12, in this study, owing to the higher current and the constraint effect by the water-cooled Cu nozzle, the maximum electrode temperature (3960 K) is much higher than the melting point of the ThO 2 emitter material With the aid of the advanced x-ray transmission system, the flow patterns of the tungsten particles in the molten pool can be clearly observed.…”
Section: Validation Of the Numerical Simulationmentioning
confidence: 99%